Early Onset Diffusion Abnormalities in Refractory Headache Disorders - Santoro, Jonathan D.; Moon, Peter K.; Han, Michelle; McKenna, Emily S.; Tong, Elizabeth; MacEachern, Sarah J.; Forkert, Nils D.; Yeom, Kristen W. (Frontiers in Neurology, 2022)
Objective: This study sought to determine if individuals with medically refractory migraine headache have volume or diffusion abnormalities on neuroimaging compared to neurotypical individuals. Background: Neuroimaging biomarkers in headache medicine continue to be limited. Early prediction of medically refractory headache and migraine disorders could result in earlier administration of high efficacy therapeutics. Methods: A single-center, retrospective, case control study was performed. All patients were evaluated clinically between 2014-2018. Individuals with medically refractory migraine headache without any other chronic medical diseases were enrolled. Patients had to have failed more than two therapeutics and aura was not exclusionary. The initial MRI study for each patient was reviewed. Multiple brain regions were analyzed for volume and apparent diffusion coefficient values. These were compared to neurotypical control data. Results: A total of 79 patients with medically refractory migraine headache were included and compared to 74 neurotypical controls without headache disorders. Comparison of individuals with medically refractory migraine headache to controls revealed statistically significant differences in median apparent diffusion coefficient (ADC) in multiple brain subregions (p < .001). Post hoc pair-wise analysis comparing individuals with medically refractory migraine headache to control patients revealed significantly increased median ADC values for the thalamus, caudate, putamen, pallidum, amygdala, brainstem, and cerebral white matter. No volumetric differences were observed between groups. Conclusions: In individuals with medically refractory migraine headache, diffusion abnormalities are present on initial neuroimaging studies. It may be possible to predict medically refractory clinical courses in individuals with migraine headache prior to medication failure using brain MRI analysis, although further study is needed.